Towards therapeutic drug monitoring of everolimus in cancer? Results of an exploratory study of exposure-effect relationship. (July 2017) - Deppenweiler, Marine; Falkowski, Sabrina; Saint-Marcoux, Franck; Monchaud, Caroline; Picard, Nicolas; Laroche, Marie-Laure; Tubiana-Mathieu, Nicole; Venat-Bouvet, Laurence; Marquet, Pierre; Woillard, Jean-Baptiste
Graphical abstract: Abstract: Introduction: Therapeutic drug monitoring (TDM) of everolimus is not performed in oncology and no trough level (C0 ) target has been yet defined. The aim of this study was to determine everolimus C0 target for toxicity and efficacy. Materials and methods: Clinical, biological and radiologic data from 54 patients were collected. Toxicity event was defined by termination, temporary interruption and/or dose reduction of everolimus while efficacy was defined as progression-free survival. C0 values were dichotomized by ROC curve analysis and the association between exposure and outcome was determined using Cox models for repeated events (toxicity) or Cox model censured at the first event (progression free survival). Results: Among the 42 patients (77.8%) with breast cancer, 10 (18.5%) kidney cancer and 2 (3.7%) neuroendocrine cancer, adverse events were reported in 75.9% of the patients (everolimus termination in 25.9% patients). C0 everolimus higher than 26.3 ng/mL (Sen = 0.38, Spe = 0.88) were associated with a 4-fold increased risk of toxicity (HR = 4.12, IC95% = [1.48–11.5], p = 0.0067) whereas C0 lower than 11.9 ng/mL were associated with a 3-fold increased risk of progression (HR = 3.2, IC95% = [1.33–7.81], p = 0.001). Discussion: Further studies are required to evaluate the everolimus C0 threshold proposed for toxicity (26.3 ng/mL) and for progression (11.9 ng/mL) especially with a large number of patients and more homogeneous types of cancer. However, these results are in favour of TDM for everolimus in oncology.